(untitled) (Global Journal of Management and Business Research, 2022)
This paper aims to assess the service quality of Sonali Bank Limited using the SERVQUAL framework to measure Tangibility, Reliability, Responsiveness, Assurance, Empathy and Overall Service Quality. A well-structured questionnaire was developed, and 200 respondents’ data were analysed with SPSS 20. Data analysis showed that Tangibility, Reliability, and Empathy positively affect Overall Service Quality, and Responsiveness and Assurance negatively impact Service Quality. Customer perception reveals that Tangibility, Reliability, and Responsiveness of Sonali Bank Limited are not satisfactory, while Assurance and Empathy are founded as moderate and satisfactory, respectively. Finally, we found that overall service quality depends on at least one of the following variables: Tangibility, Reliability, Responsiveness, Assurance, and Empathy.